Reactive silver inks for antiviral, repellent medical textiles with ultrasonic bleach washing durability compared to silver nanoparticles. - Anthony J Galante; Brady C Pilsbury; Kathleen A Yates; Melbs LeMieux; Daniel J Bain; Robert M Q Shanks; Eric G Romanowski; Paul W Leu (PLoS ONE, 2022)
Medical textiles are subject to particularly harsh disinfection procedures in healthcare settings where exposure risks are high. This work demonstrates a fabric treatment consisting of a reactive silver ink and low surface energy PDMS polymer that provides for superhydrophobicity and antiviral properties against enveloped herpes simplex virus stocks even after extended ultrasonic bleach washing. The antiviral properties of reactive silver ink has not been previously reported or compared with silver nanoparticles. The fabric treatment exhibits high static contact angles and low contact angle hysteresis with water, even after 300 minutes of ultrasonic bleach washing. Similarly, after this bleach washing treatment, the fabric treatment shows reductions of infectious virus quantities by about 2 logs compared to controls for enveloped viruses. The use of silver ink provides for better antiviral efficacy and durability compared to silver nanoparticles due to the use of reactive ionic silver, which demonstrates more conformal coverage of fabric microfibers and better adhesion. This study provides insights for improving the wash durability of antiviral silver fabric treatments and demonstrates a bleach wash durable, repellent antiviral treatment for reusable, functional personal protective equipment applications.